Diabetes in Mice after Coxsackie B4 Virus Infection. Issue 5870 (7th July 1973) - Coleman, T. J.; Gamble, D. R.; Taylor, K. W.
Abstract : The intraperitoneal inoculation of CD1 mice with Coxsackie virus B4 resulted in the raising of blood sugar levels to diabetic values 12 days after the administration of the virus. Serum insulin remained inappropriately low. Light microscopy changes in the islets of Langerhans showed mononuclear cell infiltration of the islets and marked degranulation of the β cells. The acinar tissue appeared to be little changed. It is concluded that Coxsackie B4 virus may cause a diabetic state compatible with islet cell damage.